Disminución del clearance de creatinina como factor de riesgo asociado a mortalidad en pacientes con síndrome coronario agudo. Hospital Regional Docente de Trujillo. 2005 - 2014 - Pérez Cueva, Muriel Rosalina (2015)
To determine whether the decrease in creatinine clearance is a risk factor associated with mortality in patients with Acute Coronary Syndrome. Material and Methods: A retrospective, cross – sectional, case – control study was conducted at Regional Hospital of Trujillo. The sample (n = 192) was divided into 2 groups: Group I (cases: patients with Acute Coronary Syndrome who died within 30 days after diagnosis) and Group II (control: patients with Acute Coronary Syndrome who did not die in the first 30 days after diagnosis) at a ratio of 48 and 144 patients respectively. Results: The patient stratification by sex and mortality reports a rate of 20 % of deaths in men and 32.5% in women; by age group and mortality has a rate of 5.3% in < 50 years; 16.9 % in 50 – 65 years, and 32.5% in those > 65 years. The percentage decrease in creatinine clearance in patients who died within 30 days was 97,9 % and those who did not was 84 %. Decreased creatinine clearance in patients with Acute Coronary Syndrome have an OR of 8.93 for mortality (p – value = 0, 0117, CI 95%). Conclusions: The decrease in creatinine clearance is a risk factor associated with mortality in patients with Acute Coronary Syndrome